Agroecological characteristics of dairy value chain stakeholders' business models in Bobo-Dioulasso - Sib, Ollo; OuTTARA, Désiré S.; Orounladji, Michel; Sodre, Etienne; Traore, Arahama; Sanogo, Souleymane; Corniaux, Christian; Vall, Eric (2023)
The report covers the characterization results of the current business models of stakeholders operating upstream in Bobo-Dioulasso's dairy value chain (agro-pastoral dairy farmers, mini-dairy farms, milk collection centers, independent collectors, processing units using local milk and processing units using milk powder) based on the knowledge of the industry as outlined by Sib et al. (2023). In order to confirm current business models, focus groups involving representatives of the various segments of Bobo Dioulasso's dairy value chain were set up at CIRDES (Centre International de Recherche-Développement sur l'Élevage en zone Subhumide). This helped to identify the characteristics of business models that were either aligned or at odds with the 13 elements of agroecology. The purpose of this final stage was to identify the elements that will need to be addressed in order to develop an agroecological business model for the dairy industry.